The collapse of the conventional : German film and its politics at the turn of the twenty-first century - Fisher, Jaimey; Prager, Brad, 1971- (Contemporary approaches to film and television series., 2010)
""Fisher and Prager have assembled a significant group of essays by the emerging generation of German cinema experts in the US. The anthology is the first serious attempt to retell the history of the New German Cinema and the c̀onsensus' cinema of the 1900s through the lens of contemporary, post-2000 films in all their diversity. Film scholars, students of the German cinema, and the general reading public will discover here why D̀eutsches Kino' is once again in the limelight."--Marc Silberman, chair of the Department of German at the University of Wisconsin, Madison" ""The Collapse of the Conventional offers a comprehensive introduction to contemporary German cinema and is bound to stimulate new debates about the legacies of New German Cinema and its politics of the aesthetic. A must for everyone interested in German cinema and Contemporary culture."--Sabine Hake, Texas Chair of German Literature and Culture at the University of Texas at Austin" ""Bringing together many of the most important scholars of German film, this hugely significant collection offers a fascinating and subtle account of the contours of the political in the post-Wall cinematic landscape."--Paul Cooke, professor of German cultural studies in the School of Modern Languages and Cultures, University of Leeds"--Jacket.